The Great Reset 2021 European Public Investment Outlook - Cerniglia, Floriana; Saraceno, Francesco; Watt, Andrew 1963- (Open Book Publishers, 2021)
This timely and insightful collection of essays written by economists from a range of academic and policy institutes explores the subject of public investment through two avenues. The first examines public investment trends and needs in Europe, addressing the initiatives taken by European governments to tackle the COVID-19 recession and to rebuild their economies. The second identifies key domains where European public investment is needed to build a more sustainable Europe, from climate change to human capital formation. Building on the 2020 edition, The Great Reset demonstrates the value of public capital both within European countries and as a European public good, shedding light on the impact that the NextGenerationEU’s Recovery and Resilience Facility will likely have on the macroeconomic structure of the European economy. The first part of the Outlook assesses the state of public investment in Europe at large, as well as focusing on five countries (France, Germany, Italy, Poland and Spain) as case studies. The second part focuses on the challenges posed by the pandemic and the pillars of the NextGenerationEU investment plan, with chapters ranging from education and digitalization, to territorial cohesion and green transition. This book is a must-read for economists, policymakers, and scholars interested in the impact and recovery of European countries during a time of extensive uncertainty.